(3eG dG jSY GdWHjH Lgdgs - (3jhSa Hf ESeGYjd Hf EdjGS Hf CMeO, CHh GdeMGSf, fUjQ GdOjf GdNhjj GdTGaYqj GdHZOGOj GdeYQha HGHf GdcJHj,J (B754 (3g` s ((3YeQGf Hf eMeO GdeZQHi GdTgjQ HGdZQjGfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dG Jcjag MbjbI eYQaI GdYdhe hGdCagGe hdG JMjW Hcfg PGJg GdYbhd hGdChgGe s
(3BNQgG (B:s
(3eY GYJeGOfG Ydi cKjQ ef eUfaGJ GdeHGQ aEfge GYJeOhG Pdcq s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfhGfGJ HGdMeQIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs